The ideal image of an instructor desired by students for high school baseball and ekiden clubs competing at the highest level in Japan: Focused group interviews with club members - Seino, J.; Tamura, N.; Takahashi, Y. (Japan Journal of Physical Education, Health and Sport Sciences, 2023)
High school "sports club activities" in Japan aim to achieve success in competitions, maximize individual potential, and attain excellence in sports, regardless of competitive level. Focusing particularly on high school sports clubs that were competing at the highest level in Japan, the present study attempted to clarify the ideal image of an instructor desired by member students, based on specific cases. The subjects were students belonging to the baseball club and the "ekiden" (long-distance relay race) club at private high school "A" located in the Kanto region. Based on the selection conditions, 8 subjects were chosen from each club. A survey was then conducted based on an interview guide, adopting a focus group interview format, and eliciting interactions between students. The survey date was November 28, 2021, for the baseball club and January 26, 2022, for the ekiden club. The qualitative data obtained were analyzed using the KJ method. For the baseball club, 39 codes were extracted from 85 words, and 28 lower-order categories, 8 medium-order categories, and 3 higher-order categories were generated. For the ekiden club, 27 codes were extracted from 74 words, and 19 lower-order categories, 5 medium-order categories, and 2 higher-order categories were generated. It was found that the qualities desired of an instructor were a combination of kindness like that of a family member, strictness while maintaining a stance of equality toward athletes, and psychological stability. It was also considered desirable for an instructor to respond to diverse forms of individuality at a high level in order to deepen mutual understanding between himself/herself and the athletes, and to possess instructional and organizational management skills that evolved with the times. In terms of this idealized image, there are clearly limits on what a single instructor can achieve, and therefore there will likely be a need to examine the effectiveness of systems relying on multiple experts for sports club activity instruction.